Gambaran Motivasi Orang Tua terhadap Physical Distancing pada Anak Sekolah Dasar di Tengah Pandemi Covid-19 di Kelurahan Karangrejo, Banyuwangi - Kurniawan, Widhi Cahya; Sulistyorini, Lantin; Septiyono, Eka Afdi (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is an emergence virus in the end of 2019 and causing respiratory system disorders such as severe lung infections, leading to death in all age groups including children. The purpose of this study was to determine the description of parents' motivation towards physical distancing in elementary school children during Covid-19 pandemic in Karangrejo District, Banyuwangi. This research involved 90 parents from elementary schools in Karangrejo which was chosen using purposive sampling technique. Data on parent motivation were collected using a questionnaire consisting of 3 indicators with 11 questions measured by a Likert scale. The study indicate that the motivation of parents towards physical distancing in elementary school during the Covid-19 pandemic is in the very good category, with the value interval of 30.26-35.75, and average 33.21. In conclusion, the motivation of parents towards physical distancing in elementary school children in Karangrejo village is very good. This research is expected to be the basis for child caregivers in the community to identify parents' motivation attitudes.